Pharmacist recommendations for carbapenem de-escalation in urinary tract infection within an antimicrobial stewardship program - Svetlana Sadyrbaeva-Dolgova; Pilar Aznarte-Padial; Alberto Jimenez-Morales; Manuela Expósito-Ruiz; Miguel Ángel Calleja-Hernández; Carmen Hidalgo-Tenorio (Elsevier, 2020)
Background: Carbapenem antibiotics are considered the treatment of choice for serious extended-spectrum beta-lactamase-producing Gram-negative bacteria infections. Our objectives were to analyze the results of carbapenem de-escalation therapy in complicated urinary tract infections (UTIs) attended in a third-level Spanish hospital and to evaluate the impact of pharmacist recommendation in this practice, the outcomes obtained, and associated factors. Methods: This prospective observational study of carbapenem prescriptions and de-escalation performance was conducted in a third-level hospital between August 1 2013 and July 31, 2014. Data were gathered on carbapenem treatment duration, de-escalation, length of hospital stay, mortality rate, and associated re-admissions. Results: De-escalation, which was only ordered for patients with positive cultures, was conducted in 49.7% of the 163 patients with complicated UTI. More than half (69.1%) of pharmacist interventions were accepted. De-escalation reduced the median hospital stay by five days (p = 0.030). Crude hospital mortality was lower in the de-escalation group (7.4% vs. 29.3%, p < 0.001), although their exposure to carbapenems was lower (4 vs 6 days, p < 0.001).Factors associated with de-escalation were ICU stay for at least 48 h, pharmacist recommendation and ESBL or AmpC producing Enterobacteriaceae. Factors associated with in-hospital mortality were age, previous admission and duration of hospital stay, but not pharmacist recommendation. Otherwise, carbapenem de-escalation was associated as a protective factor against in-hospital mortality. Conclusions: Carbapenem de-escalation in accordance with pharmacist recommendation proved to be a safe approach in complicated UTI, reducing the hospital stay of patients without affecting the re-admission rate. Keywords: De-escalation, Carbapenems, Urinary tract infection, Antimicrobial stewardship programs, Pharmacist recommendations